Using RetinoGraphics BPI-50 in Selected Canine Eye Disorders - Pamuk, Kamuran (Progress in Nutrition, 2021)
Study Objectives: The objective of this study was to assess pupillary light reflexes under pen light, red light, and blue light stimuli of different intensities in the healthy eyes of dogs and the eyes of dogs with cataracts. The study examines patients with cataracts and evaluates whether there is retinal or optic nerve damage based on the pupillary response. Methods: This study used 10 healthy dogs and 10 dogs with cataracts at different stages that were sedated with tomidine (5 µg/kg). The RetinoGraphics BPI-50 (Precision Illuminator) device was used for light stimulation. Light intensities comprised pen light 570 nm (nominal), red 660 nm and blue 465 nm wavelengths. Results: The measurements by the illuminator BPI-50 with red light and blue light source revealed that the pupil diameters ​​of dogs with incipient and immature cataracts showed similarity with the eyes of healthy dogs. Under pen light and red light illumination, the pupil diameters of the dogs with mature and hypermature cataracts were similar to those obtained without using any light source. Under the blue light source, in turn, there was a significant reduction in pupil diameter. Conclusion: As an alternative to the advanced imaging techniques used in eye examination, RetinoGraphics BPI-50 (Precision Illuminator) can be used to assess pupillary light reflex for pre-diagnostic purposes. A blue light source can be used in mature and immature animals in cases where the pupillary reflex created by pen light is insufficient.